Development of Interactive Multimedia Based on Ethnoscience to Improve Student Learning Outcomes in the Science Subject Style Material for Grade IV Elementary School: Indonesia - Putu Ayu Adi Sawitri; Ni Wayan Rati; Adrianus I Wayan Ilia Yuda Sukmana (Undiksha Press, 2025)
The problem in science and social studies (IPAS) learning at the elementary level, particularly in the topic of force, lies in the lack of contextual learning media that actively and enjoyably engage students. This condition has led to low student learning outcomes. This study aims to examine the validity, practicality, and effectiveness of ethnoscience-based interactive multimedia in enhancing students’ learning outcomes. This research is a type of research and development (R&D) employing the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included one fourth-grade teacher, two experts (media and content), and 28 fourth-grade elementary students. Data were collected using validation questionnaires, practicality questionnaires, and learning outcome tests (pretest and posttest) with a one-group pretest-posttest design. The data were analyzed using descriptive quantitative techniques. The results indicated that the developed interactive multimedia is highly valid, highly practical, and effective, as evidenced by a significant increase in students’ learning outcome scores. It can be concluded that ethnoscience-based interactive multimedia serves as a contextual alternative learning medium that supports local cultural integration in meaningful and sustainable IPAS learning processes.